PECULIARITIES OF OPERATIONAL ACTIVITIES OF THE ENTERPRISE IN THE WATER SUPPLY AND SEWERAGE SECTOR DURING THE WAR - Овецька, Ольга; Льохерт, Маркіян Володимирович (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The purpose of this article is to analyse the current state of the centralised water supply and centralised wastewater disposal sector of the housing and communal services in Lviv region and to study the peculiarities of the enterprise’s operational activities (on the example of Lvivvodokanal) under martial law. The provision of settlements in Lviv region with centralised water supply and centralised sewerage services is analysed. A comparative description of the main production indicators of water supply in 2021/2022 in the region is provided. The structure of Lvovvodokanal’s tariffs in 2022 for centralised water supply and sewerage services and the factors that influenced the change in tariffs, in particular, a decrease in sales volumes, are investigated. Based on the results of the research, the following conclusions were made: legislative changes in the procedure for paying for housing and communal services during martial law (regarding debt collection, charging citizens with fines or penalties for untimely payment of communal services, stopping the provision of such services during martial law, etc.) impose an additional burden on the results of the operational activities of housing and communal services enterprises and make it impossible to fully reproduce and modernize worn- out objects of critical infrastructure; improvement of the operational activities of enterprises in the centralized water supply and drainage sector and the realization of development potential are impossible without taking into account the features of current tariffs and reorganization measures to achieve its strategic goals: balancing the tariff policy, adopting economically justified tariffs will allow enterprises to carry out reconstruction of centralized water supply and centralized water drainage systems and ensure proper the level of service provision and high quality of water in accordance with the goals and objectives of the National Targeted Social Program "Drinking Water of Ukraine", the Global Goals of the UN Sustainable Development (6th goal "Clean water and proper sanitary conditions") according to the key indicators of the national system of SDG.